Evaluation criteria for transport: an analysis of local policy implementation towards sustainable residential development - Yanuaria, Cathrina (Curtin University, 2004)
One of the most important issues influencing urban areas is that of sustainable residential development. In this regard, formulation and implementation of policies relating to transport play a major role in decreasing the amount of energy consumed and greenhouse gases released into the atmosphere. This awareness of the major role of transport posed the main research question “Have transport elements in policies for residential development in Western Australia been implemented on the ground in the Perth Metropolitan Region?” Since this study focuses on and evaluates the implementation of residential planning policy on the ground at local level, it uses case study areas (Joondalup and Woodlake) deemed benchmark of sustainable development within the Perth Metropolitan Region in Western Australia. Policies for residential development and sections on transport (towards sustainable development) were collected and from this, evaluation criteria were drawn to be measured against their implementation. Then, field observation, and household questionnaire surveys were conducted to check and identify the extent of implementation. Subsequently, semi-structured interviews with policy players were undertaken to clarify findings and factors influencing (impeding or supporting) policy implementation. The findings of this research indicate that Joondalup (planned and developed more than two decades ago) was more sustainable in transport terms than Woodlake (developed nearly a decade ago) when measured against policies at the time of the planning and development phases. But when the case study areas were measured against current policy objectives and new evaluation criteria for transport towards sustainable development, Woodlake performs better.It may not be surprising that in future Woodlake might be considered less sustainable than it is now. It signifies that policies and residential planning standards have improved to a certain degree over time. Improvement is also apparent in the translation of international and national policies to lower-level policies. Recommendations propose what could be performed better in future, based on what has been learnt from past experience.